2020
DOI: 10.1186/s12576-020-00752-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane current evoked by mitochondrial Na+–Ca2+ exchange in mouse heart

Abstract: The electrogenicity of mitochondrial Na +-Ca 2+ exchange (NCXm) had been controversial and no membrane current through it had been reported. We succeeded for the first time in recording NCXm-mediated currents using mitoplasts derived from mouse ventricle. Under conditions that K + , Cl − , and Ca 2+ uniporter currents were inhibited, extramitochondrial Na + induced inward currents with 1 μM Ca 2+ in the pipette. The half-maximum concentration of Na + was 35.6 mM. The inward current was diminished without Ca 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Recently, the inward current through mNCX was measured from a mitoplast preparation (Islam et al . 2020). This study showed that the mNCX current is instantaneously activated upon hyperpolarization of mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the inward current through mNCX was measured from a mitoplast preparation (Islam et al . 2020). This study showed that the mNCX current is instantaneously activated upon hyperpolarization of mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Kim & Matsuoka, 2008), which provides us with little information on the activation kinetics of mNCX because the mitochondrial Ca 2+ buffering properties are largely unknown. Recently, the inward current through mNCX was measured from a mitoplast preparation (Islam et al 2020). This study showed that the mNCX current is instantaneously activated upon hyperpolarization of mitochondrial membrane potential.…”
Section: Specificity Of Tpp + Effectsmentioning
confidence: 98%
“…The use of permeabilized rat ventricular myocytes demonstrated that the NCXm is voltagedependent and electrogenic, suggesting a stoichiometry higher than 3Na + for one Ca 2+ (Kim & Matsuoka, 2008). This stoichiometry and the electrogenic nature of the NCXm were proved recently using the whole-mitoplast patch-clamp technique (Islam, Takeuchi & Matsuoka, 2020). Detailed mechanisms of the regulation of NCXm activity and sensitivity to effectors have not yet been clarified, but some studies demonstrate its regulation by a stomatin-like protein 2 (Da Cruz et al, 2010) and the mitochondrial phosphatase and tensin homolog deleted on chromosome 10 (PTEN)induced kinase 1 (PINK1) (Gandhi et al, 2009).…”
Section: The Mptp and Mitochondrial Ca 2+ Uptake Or Overloadmentioning
confidence: 84%
“…In order to overcome this problem, it is necessary to clamp ∆Ψ. Recently, our group succeeded in recording membrane currents through NCX mit in mouse cardiac mitochondria using whole-mitoplast patch clamp methods, thus settling the controversy [ 8 ].…”
Section: Biophysical Properties Of Ncx Mitmentioning
confidence: 99%